Complications After Continuous Posterior Lumbar Plexus Blockade for Total Hip Arthroplasty: A Retrospective Cohort Study. Issue 4 (1st July 2017) - Njathi, Catherine W.; Johnson, Rebecca L.; Laughlin, Ruple S.; Schroeder, Darrell R.; Jacob, Adam K.; Kopp, Sandra L.
Abstract : Background and Objectives: While benefits of regional anesthesia in total hip arthroplasty (THA) are well documented, data describing the incidence of complications related to the use of posterior lumbar plexus blockade for THA remain limited. Our primary aim was to evaluate the incidence of infectious, bleeding, and neurological complications related specifically to the use of continuous posterior lumbar plexus block for elective THA. Methods: We reviewed the electronic medical records of all adult patients who underwent elective THA with continuous posterior lumbar plexus blockade between December 1, 2004, and April 30, 2015, using the Mayo Clinic Total Joint Registry. All complications were verified via manual chart review by 2 reviewers. Patient demographics, type of surgery, and complications were analyzed. Results: A total of 9649 patients who underwent 11, 395 THA procedures met the inclusion criteria. There were 8686 (76.2%) primary and 2709 (23.8%) revision THAs. There were no block-related infections (0.00%; 95% confidence interval [CI], 0.00%–0.03%) and only 1 block-related hematoma (0.01%; 95% CI, 0.00%–0.05%) in a patient with multiple risk factors for bleeding. There were 60 (0.53%; 95% CI, 0.40%–0.68%) perioperative nerve injuries. Forty-three were in the sciatic distribution (71.67%; incidence, 0.38%). Although there were no documented overt iatrogenic nerve injuries, the posterior lumbar plexus blockade could not be excluded as the potential cause in 9 cases (incidence, 0.08%) based on clinical distribution or electromyographic findings. Conclusions: In our large, single-center cohort study, we report no catheter-related infections, whereas catheter-related hemorrhagic and neurological complications also appear to be rare.